Infectious Process and Sepsis 2020
DOI: 10.5772/intechopen.90572
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Gene Polymorphism and Sepsis

Abstract: Trauma is a significant problem across the globe with mortality more than 50%. Despite the advancement of pre-hospital care to trauma patients, early resuscitation in the emergency department, surgical interventions and intensive care monitoring mortality rate has not improved yet. The higher rate of mortality in trauma patients is usually associated with development of complications such as sepsis, septic shock, and MOF which may occur due to hysterical immune inflammatory responses. Trauma patients who devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…In the case of trauma hemorrhage patients, a study demonstrated that Th type 1 cell (Th1) responses (secrete IL-2, IFNγ) were suppressed. In contrast, the Th type 2 (Th2) responses (secrete IL-4, IL-5, IL-13 and IL-10) were elevated, leading to a suppressed adaptive immune response and increased susceptibility to sepsis [ 35 ]. Findings from another group indicate that following severe burn trauma, a notable increase in Th2 response occurs without altering the Th1 response [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of trauma hemorrhage patients, a study demonstrated that Th type 1 cell (Th1) responses (secrete IL-2, IFNγ) were suppressed. In contrast, the Th type 2 (Th2) responses (secrete IL-4, IL-5, IL-13 and IL-10) were elevated, leading to a suppressed adaptive immune response and increased susceptibility to sepsis [ 35 ]. Findings from another group indicate that following severe burn trauma, a notable increase in Th2 response occurs without altering the Th1 response [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%